2016
DOI: 10.1016/j.sajb.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Shoot regeneration from leaf explants of Withania coagulans (Stocks) Dunal and genetic stability evaluation of regenerates with RAPD and ISSR markers

Abstract: Edited by J Van StadenKeywords: Endangered Ex vitro Leaf regeneration Vegetable rennet and withanolides Withania coagulans (Stocks) Dunal (Solanaceae) is a critically endangered medicinal plant known for its multiple medicinal properties. We report here an efficient and high frequency plantlet regeneration system through direct organogenesis in W. coagulans using in vitro-derived leaves as explants. On Murashige and Skoog's (MS) medium containing 4.44 μM 6-benzylaminopurine (BAP) 73.7 ± 4.3% explants responded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…The RAPD marker has been utilized in detecting genetic variability in several species of plants [8][9][10][11][12]. The ISSR marker has been also proven to provide a strong, reproducible, easy, fast and economical means to evaluate genetic variability and identify variations between narrowly associated genotypes in several species of plants [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The RAPD marker has been utilized in detecting genetic variability in several species of plants [8][9][10][11][12]. The ISSR marker has been also proven to provide a strong, reproducible, easy, fast and economical means to evaluate genetic variability and identify variations between narrowly associated genotypes in several species of plants [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results of regeneration from leaf explants using TDZ has been reported in primrose (Gyves et al, 2001), mulberry (Chitra and Padmaja, 2005), Paulownia tomentosa (Corredoira et al, 2008) and Jatropha curcus (KhuranaKaul et al, 2010), which are in agreement with our results. Similarly, In vitro shoot regeneration has also been reported in plants of family Solanaceae (Magioli et al, 1998;Mallaya and Ravishankar, 2013;Rathore et al, 2016). While, Hussain et al (2005) reported that field grown explants of different varieties of S. tuberosum had high regeneration potential.…”
Section: Discussionmentioning
confidence: 77%
“…High concentration of TDZ resulted in hyperhydricity of shoots reported in Pluchea lanceolata (Kher et al 2014). TDZ at a higher concentration resulted in callus formation from leaf explants derived from in vitro raised shoots in W. coagulans is reported recently by Rathore et al (2016). Effectiveness of mT for axillary shoot multiplication and adventitious regeneration is reviewed by Aremu et al (2011).…”
Section: Resultsmentioning
confidence: 97%